Effectiveness of Motivational Educational Videos on Knowledge, Body Mass Index, Self-Care, and Empowerment among Older Women with Hypertension - Rosiana Eva Rayanti; Istananda Tirtaning Nugraheni; Indera Aini (Jurnal Keperawatan Profesional, 2026)
Hypertension is a non-communicable disease with a high risk of mortality worldwide. According to the 2023 RKPD Report of Salatiga City, the prevalence of hypertension increased from 0.60% in 2020 to 0.72% in 2021. This rise is partly attributed to the low public awareness of hypertension, resulting in decreased interest in practicing self-care management for the condition. This study aimsto describe the effect of motivational educational videos on knowledge, body mass index, self-care, and health care empowerment among elderly individuals with hypertension in Salatiga City. The research employed a quasi-experimental design with a two-group pre–post-test approach, involving 20 elderly participants in the experimental group and 15 in the control group, aged 60–79 years, using a purposive sampling technique. Research instruments included validated and reliable questionnaires assessing knowledge, self-care, and healthcare empowerment. Data were analyzed using MANOVA. The  results showed that improvements in the control group were considerably less than those in the experimental group. The MANOVA test revealed significant differences between the experimental and control groups in systolic blood pressure, knowledge about hypertension, self-care profile, and health care empowerment. The contextual audiovisual educational intervention provided to the experimental group was effective in enhancing cognitive and behavioral aspects related to hypertension management.